Introduction to microcontrollers architecture, programming, and interfacing for the Freescale 68HC12 - Lipovski, G. Jack
This book is a comprehensive, introductory text/reference for electrical and computer engineers and students with little experience with a high-level programming language. It systematically teaches the programming of a microcontroller in assembly language, as well as C and C++. This books also covers the principles of good programming practice through top-down design and the use of data structures. It is suitable as an introductory text for a first course on microcomputers that demonstrates what a small computer can do. Shows how a computer executes instructions; Shows how a high-level programming language converts to assembler language; Shows how a microcontroller is interfaced to the outside world; Hundreds of examples, experiments, "brain-teasers" and motivators; More than 20 exercises at the end of each chapter; Complete solutions manual available for Instructors; CD includes example code from book as well as the MetroWerks CodeWarrior C++ compiler.